Uporaba cvetnonedeljskih butar na slovenskem podeželju - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2009)
The article presents the use of Palm Sunday bundles in the Slovene countryside. Because of the belief in the magic power the bundles obtained when they were blessed and the conviction that they were capable of transferring this special power elsewhere, the bundles were used to protect homes, domestic animals, land, and crops. They were further used in many customs and to heal people and animals. After the Second World War, the belief in the magic power of Palm Sunday bundles started to decline, but they acquired new functions in the late 20th century.
Keywords: ethnology; etnologija; ljudski običaji; Public holidays in Slovenia; velika noč; cvetna nedelja; Slovenci; Slovenes; rural area; podeželje; zgodovinski pregledi